2019
DOI: 10.1111/jonm.12737
|View full text |Cite
|
Sign up to set email alerts
|

Meaning in life and self‐esteem help hospice nurses withstand prolonged exposure to death

Abstract: Aim The purpose of this study was to investigate relationships between the presence of and search for meaning in life and self‐esteem, psychological distress, burnout and affect among hospice nurses. Background The nature of hospice nursing may prompt existential concerns. Method Hospice nurses (N = 90) completed an online survey. Results The presence of meaning in life was associated with lower psychological distress, burnout and negative affect, and higher levels of positive affect, whereas the search for me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 34 publications
3
52
0
5
Order By: Relevance
“…When hospice nurses have a sense of purpose or meaning in their lives, this enhances self-esteem and buffers against potential negative outcomes following exposure to stress 59. However, this review identified the importance of making sense of stressful experiences at work (rather than in life) and developing a sense of meaning or purpose in their role.…”
Section: Discussionmentioning
confidence: 95%
“…When hospice nurses have a sense of purpose or meaning in their lives, this enhances self-esteem and buffers against potential negative outcomes following exposure to stress 59. However, this review identified the importance of making sense of stressful experiences at work (rather than in life) and developing a sense of meaning or purpose in their role.…”
Section: Discussionmentioning
confidence: 95%
“…Other authors said that the feeling of having good health was negatively correlated with burnout in palliative care nurses [ 31 ]. Another study informed that EE was negatively correlated with having a meaning of life and positive affect [ 30 ], while psychological distress and negative affect were positively correlated with EE [ 30 ]. In this sense, having a meaning in life and a good self-esteem explained the variance of EE in a 3–16% [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another study informed that EE was negatively correlated with having a meaning of life and positive affect [ 30 ], while psychological distress and negative affect were positively correlated with EE [ 30 ]. In this sense, having a meaning in life and a good self-esteem explained the variance of EE in a 3–16% [ 30 ]. Furthermore, burnout levels were lower in nurses with higher levels of psychological hardiness and psychological empowerment [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nurses may express a variety of emotions and attitudes related to end-of-life care (1,6) , which are particularly stressful because they are constantly interpreting grief or death as a personal failure (7) . Some authors (8) stated that nurses require a wide range of skills to properly deal with death and manage their own fears, beliefs, and attitudes towards dying patients (9) .…”
Section: Introductionmentioning
confidence: 99%